Antimicrobial Activity of Some Derivatives of 1,4-Dihydropyridines - Prabha Mehta; Prabha Verma (Journal of Chemistry)
Hantzsch reported the synthesis of functionalized 1,4-dihydropyridines via three-component condensation of an aromatic aldehyde, ketoester, and ammonium hydroxide. This multicomponent reaction is of much importance due to excellent pharmacological properties of dihydropyridines. In this account, we synthesized some halo- and nitrophenyl dihydropyridines and evaluated their antimicrobial activity. The minimum inhibitory concentration (MIC) was determined by microdilution technique in Mueller Hinton broth. The MICs were recorded after 24 hours of incubation at 37°C. These results showed that these compounds exhibited significant to moderate activities against both Gram-(+) and Gram-(−) organisms.